TRADISI "NYARANG HUJAN" MASYARAKAT MUSLIM BANTEN - Eneng Purwanti (Al Qalam, 2013)
The tradition of nyarang hujan, asking help of pawang to restrain or to move rain, is still used by Muslim society in Cimanuk Pandeglang Banten. It is usually performed when they will conduct a celebration (hajatan) by a hope that the rain will not drop when the ceremony is going on. This article is a result of field research aimed at understanding the phenomenon of such a tradition by using social approach. Obseroation and in-depth interoiews with the performers of the tradition of nyarang hujan are used to collect the data. This research shows that there is an acculturation process between Islamic values and local tradition in this phenomenon. Most people of Cimanuk society believe that Allah who has power to drop and stop rain; however, they have to do some efforts, called nyare'at, to achieve their hope through a pawang's pray. Key Words: Tradition of nyarang hujan, pawang, Muslim, Cimanuk, Banten